Evaluation of the enhancement of photosynthetic rate in a komatsuna (Brassica rapa L. var. perviridis) canopy with upward lighting using an optical simulation in a plant factory with artificial light - Saito, Kota; Goto, Eiji (Frontiers in Plant Science, 2023)
In a plant factory with artificial light (PFAL), upward lighting is expected to prevent senescence and decrease in the photosynthetic capacity of the lower leaves in the canopy. Upward lighting may also increase the photosynthetic rate of a canopy by improving its photosynthetic photon flux density (PPFD) distribution. However, the net photosynthetic rate (Pn) of leaves is lower when the abaxial surface is irradiated than that when the adaxial surface is irradiated. The aim of this study was to estimate the PPFD in a PFAL and the Pn of plants using three-dimensional plant models and optical simulation. First, we measured the Pn of komatsuna (Brassica rapa L. var. perviridis) leaves under different conditions of the proportion (pad) of PPFD on the adaxial surface to total PPFD on both surfaces and developed an equation for the light response curve of photosynthesis considering pad. When PPFD was low, except when it was 30 and 70 µmol m−2 s−1, Pn increased as pad increased, because the absorptance also increased with pad. Under high PPFD conditions, Pn was maximized at 67–83% of pad because the light would be distributed more efficiently for photosynthesis. Next, using optical simulation and the developed equation, we estimated the photosynthetic rate of a komatsuna canopy (CPn) under downward and upward lighting. The CPn increased by 1.08–1.13 times by combining downward and upward lighting due to the increase in the photosynthetic photon flux (PPF) of light incident on the canopy and the decrease in the spatial variation of PPFD on the leaves in the canopy. As the depreciation of lamps for upward lighting accounts for 7.5–9.0% of the production cost in a PFAL, even if the depreciation of lamps for upward lighting increased, enhancement of CPn by upward lighting would be cost-effective. We performed optical simulations under 220 conditions and evaluated them using CPn as an index. Moreover, we provided the proportion of PPF of upward lighting that improved CPn and discussed the reason for this improvement. The result shows that optical simulation is useful for evaluating the lighting design in a PFAL and analyzing the effects of the lighting design on the light environment and photosynthesis.